Characterization of NAC family genes in Salvia miltiorrhiza and NAC2 potentially involved in the biosynthesis of tanshinones. (November 2021) - Zhang, Haihua; Xu, Jinfeng; Chen, Haimin; Jin, Weibo; Liang, Zongsuo
Abstract: The NAC (NAM, ATAF, and CUC) family members are specific transcription factors in plants. The large family is involved in many plant growth and developmental processes, as well as in abiotic/biotic stress responses. It has been well studied in the genomes of various plants, including Arabidopsis thaliana, tomato, and quinoa. However, identification and functional studies of NAC family members in medicinal Salvia miltiorrhiza are limited. Here, we systematically identified 84 NAC genes and named them according to their gene IDs in the recently sequenced genome. The phylogeny of NAC family protein sequences was analyzed using bioinformatics methods, which divided them into nine subfamilies. Then, their chromosomal locations, gene structures and conserved domains were analyzed comprehensively. To further investigate the regulatory functions of NACs in S. miltiorrhiza, we analyzed the response of 10 selected NAC genes to methyl jasmonate and used NAC2 for transgenic experiments. The overexpression of Sm-NAC2 decreased the tanshinone I and IIA contents by 56% and 62%, respectively. However, Sm-NAC2-RNAi promoted the accumulation of four tanshinones, tanshinone I, tanshinone IIA, cryptotanshinone, and dihydrotanshinone I, which increased 3.68-, 4.1-, 3.13- and 5.9- fold, respectively, compared with wild type. In the tanshinone biosynthetic pathways, the overexpression of Sm-NAC2 down-regulated CYP76AH1, and the silencing of Sm-NAC2 up-regulated the expression levels of HMGR1, DXS2, KSL2, and CYP76AH1. This study provides information on the evolution of Sm-NAC genes and their possible functions, and it lays a foundation for further research into the NAC family-associated regulation of tanshinone biosynthesis. Graphical abstract: Image 1 Highlights: A total of 84 NAC genes were identified in S. miltiorrhiza and divided into nine subfamilies. It was found that 10 Sm-NAC genes were differentially expressed in the roots of S. miltiorrhiza using transcriptome data. Sm -NAC2 negatively regulates the biosynthesis of tanshinones.